The efficacy of antipsychotics in the treatment of physical aggressive behavior in patients with dementia in nursing homes - Sina Nawzad; Wiepke Cahn; Heshu Abdullah-Koolmees (SAGE Publishing, 2022)
Patients with dementia often suffer from behavioral changes. A common behavioral change is acute physical aggressive behavior which is the most distressing change. This can lead to harm, which is especially problematic in nursing homes. Despite the serious safety concerns, antipsychotics are often prescribed to combat this problem. This article is aimed to review the evidence of the efficacy of utilizing antipsychotics in acutely treating physical aggressive behavior in patients with dementia in nursing homes. Therefore, a systematic literature search was performed. The results demonstrated that a meta-analysis confirmed statistically significant reduction in physical aggression when risperidone was compared to placebo. However, a randomized controlled trial showed no change in physical aggressive behavior between quetiapine and placebo. More research is needed to fully investigate the benefits of physical aggressive behavior and safety concerns of all the antipsychotics in patients with dementia in nursing homes.